0.5 V Differential Difference Transconductance Amplifier and Its Application in Voltage-Mode Universal Filter - Fabian Khateb; Montree Kumngern; Tomasz Kulej; Dalibor Biolek (My University, 2022)
This paper presents an innovative CMOS structure for Differential Difference Transconductance Amplifiers (DDTA). While the circuit operates under extremely low voltage supply 0.5 V, the circuit's performance is improved thanks to using the multiple-input MOS transistor (MI-MOST), the bulk-driven, self-cascode and partial positive feedback (PPF) techniques. As a result, the DDTA structure is less complex, with high gain of 93 dB, wide input voltage range nearly rail-to-rail, and wide transconductance tunability. As an example of application, a second-order voltage-mode universal filter using three DDTAs and two 6 pF integrated capacitors is presented. The filter is designed such that no matching conditions are required for the input and passive components, and the input signals need not be inverted. The natural frequency and the quality factor can be set orthogonally while the natural frequency can be electronically controlled. The circuit was designed and simulated in Cadence environment using $0.18 \mu \text{m}$ TSMC technology. The simulation results including intensive Monte-Carlo (MC) and process, temperature, voltage (PVT) analysis confirm the stability and the robustness of the design to process, mismatch variation and PVT corners.
Keywords: Transconductance; Operational transconductance amplifier; Cascode; Analog and Mixed-Signal Circuit Design